Success Factors in the Internalisation of Export Companies in Colombia - Escandon-Barbosa, Diana; Estrada Ochoa, Adriana (Economy of Regions, 2021)
Export success is one of the key aspect of economic growth of a country because it is the principle means of specialising, developing economies of scale, accessing new technologies and attracting foreign investment. For this reason, the significance of this topic has encouraged scientists to investigate the main factors that play a part in the development and application of successful export strategies. This article analyses the export success of Colombian businesses from the behaviour of variables at the business and sectoral levels. The research aims to characterise the relevant conditions affecting the entry of small and medium-sized enterprises (SMEs) into the foreign market, which can be useful for business owners who are in the process of internationalisation; they can also be considered as an instrument for developing policies promoting exports from Colombia. A multilevel model is estimated for a sample of Colombian businesses. We examined international experience, export commitment and export strategy as business factors that positively influence export success, as well as export assistance programmes, networks, tariff legislation, sector size and innovation as sectoral factors. It was concluded that the export destination, the country’s conditions and regulations should be examined before the beginning of the export process. However, Colombian exporters usually choose international destinations without such an analysis. In addition, government support through programmes and tariff legislation leads to greater business dynamism, favours entry into new markets and helps compensate negative results of international destinations.